X-chromosome gene dosage as a determinant of impaired pre and postnatal growth and adult height in Turner syndrome. Issue 3 (March 2016) - Fiot, Elodie; Zenaty, Delphine; Boizeau, Priscilla; Haigneré, Jeremy; Dos Santos, Sophie; Léger, Juliane; ,
Abstract : Objective: Short stature is a key aspect of the phenotype of patients with Turner syndrome (TS). SHOX haploinsufficiency is responsible for about two-thirds of the height deficit. The aim was to investigate the effect of X-chromosome gene dosage on anthropometric parameters at birth, spontaneous height, and adult height (AH) after growth hormone (GH) treatment. Design: We conducted a national observational multicenter study. Methods: Birth parameter SDS for gestational age, height, and AH before and after GH treatment respectively, and height deficit with respect to target height (SDS) were classified by karyotype subgroup in a cohort of 1501 patients with TS: 45, X (36%), isoXq (19%), 45, X/46, XX (15%), XrX (7%), presence of Y (6%), or other karyotypes (17%). Results: Birth weight, length ( P <0.0001), and head circumference ( P <0.001), height and height deficit with respect to target height (SDS) before GH treatment, at a median age of 8.8 (5.3–11.8) years and after adjustment for age and correction for multiple testing ( P <0.0001), and AH deficit with respect to target height at a median age of 19.3 (18.0–21.8) years and with additional adjustment for dose and duration of GH treatment ( P =0.006), were significantly associated with karyotype subgroup. Growth retardation tended to be more severe in patients with XrX, isoXq, and, to a lesser extent, 45, X karyotypes than in patients with 45, X/46, XX karyotypes or a Y chromosome. Conclusion: These data suggest that haploinsufficiency for an unknown Xp gene increases the risk of fetal and postnatal growth deficit and short AH with respect to target height after GH therapy.